2017
DOI: 10.5935/0004-2749.20170036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity on retrobulbar flow hemodynamics: color Doppler ultrasound evaluation

Abstract: Obese patients have a higher mean IOP and lower flow velocity than non-obese patients. Increased IOP together with decreased retrobulbar blood flow, particularly in obese individuals, may increase the risk of glaucoma development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…These results were consistent with our previous study, 22 suggesting that we must take SSI value into consideration when comparing retinal VD values. Although obesity was found to be associated with reduction of retrobulbar blood flow velocity, 28 our results did not suggest any correlation between BMI nor waist circumference and NFLP VD. In this study, there were only 70 (5%) participants having a BMI ≥30 kg/m 2 , 25 (5%) men having a waist circumference >102 cm and 204 (23%) women having a waist circumference >88 cm.…”
Section: Clinical Sciencecontrasting
confidence: 92%
“…These results were consistent with our previous study, 22 suggesting that we must take SSI value into consideration when comparing retinal VD values. Although obesity was found to be associated with reduction of retrobulbar blood flow velocity, 28 our results did not suggest any correlation between BMI nor waist circumference and NFLP VD. In this study, there were only 70 (5%) participants having a BMI ≥30 kg/m 2 , 25 (5%) men having a waist circumference >102 cm and 204 (23%) women having a waist circumference >88 cm.…”
Section: Clinical Sciencecontrasting
confidence: 92%
“…The exact pathophysiology of elevated IOP in obesity remains unclear. Possible mechanisms that can explain such association include: obesity-related oxidative stress [ 26 ] leading to trabecular meshwork malfunctioning [ 27 ], increased orbital fat impeding aqueous outflow [ 28 ], and dysregulation of retrobulbar blood flow [ 29 ].…”
Section: Obesity and Energy Intakementioning
confidence: 99%
“…When we compare the morbid obese studies' results with this current study, we observed that the CRA-PSV tends to be the more affected subparameter in relation to the severity of the obesity among the retrobulbar blood ow parameters and without a vascular resistance change in less obese cases. Similarly, another study has found a decrease only in the OA PSV and EDV values together with decreased CRA PI in morbidly obese patients [7]. On the other hand, the elevated blood cell count, hemoglobin and hematocrit values in obese patients result in an increase in the blood viscosity [19].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have focused on retrobulbar ocular blood ow or choroidal thickness changes, but not both. Only two previous studies have evaluated the effect of obesity on retrobulbar ocular blood ow, and these have only included morbid obese patients [6,7]. The above parameters are clinically important as they are part of the ocular circulation, and are also essential in guiding the clinical approach to whether subjects suffering from obesity of various degrees have an increased risk of ocular pathology development.…”
Section: Introductionmentioning
confidence: 99%